Primary Intraparenchymal Squamous Cell Carcinoma of the Kidney: A Rare and Unique Entity - Prithwijit Ghosh; Kaushik Saha (Case Reports in Pathology)
Primary squamous cell carcinoma (SCC) of the renal parenchyma is a very unusual entity which needs to be differentiated from primary SCC of renal pelvis, SCC from another primary site, and urothelial carcinoma with extensive squamous differentiation. We are most probably describing the second case of primary SCC of the renal parenchyma in a 51-year-old male who presented with heaviness of right upper abdomen with intermittent pain in right flank. Contrast-enhanced computed tomography (CECT) revealed a mass in the right lower pole of the kidney and histopathology following nephrectomy displayed the features of well-differentiated squamous cell carcinoma without urothelial involvement.